An archaeal family-B DNA polymerase variant able to replicate past DNA damage: occurrence of replicative and translesion synthesis polymerases within the B family - Jozwiakowski, Stanislaw K. (Oxford University Press, 2014)
A mutant of the high fidelity family-B DNA polymerase from the archaeon Thermococcus gorgonarius (Tgo-Pol), able to replicate past DNA lesions, is described. Gain of function requires replacement of the three amino acid loop region in the fingers domain of Tgo-Pol with a longer version, found naturally in eukaryotic Pol ζ (a family-B translesion synthesis polymerase). Inactivation of the 3′–5′ proof-reading exonuclease activity is also necessary. The resulting Tgo-Pol Z1 variant is proficient at initiating replication from base mismatches and can read through damaged bases, such as abasic sites and thymine photo-dimers. Tgo-Pol Z1 is also proficient at extending from primers that terminate opposite aberrant bases. The fidelity of Tgo-Pol Z1 is reduced, with a marked tendency to make changes at G:C base pairs. Together, these results suggest that the loop region of the fingers domain may play a critical role in determining whether a family-B enzyme falls into the accurate genome-replicating category or is an error-prone translesion synthesis polymerase. Tgo-Pol Z1 may also be useful for amplification of damaged DNA.